Continuous Assessment of Gastric Motility and Its Relation to Gastric Emptying in Adult Critically Ill Patients. Issue 8 (11th November 2020) - Goelen, Nick; Janssen, Pieter; Tack, Jan; Morales, John; Honinx, Tine; Van den Berghe, Greet; Casaer, Michael P.; Gunst, Jan
Abstract: Background: Critically ill patients frequently develop feeding intolerance, which is difficult to predict. In healthy subjects, gastric motility, assessed by nasogastric balloon tube, correlated with gastric emptying. We now investigated this correlation in critically ill patients, as well as the feasibility and safety of such application in a pilot study. Methods: Endotracheally intubated adults scheduled to receive enteral nutrition (EN) were included. After insertion of a double‐lumen nasogastric balloon tube and radiographic confirmation of position, balloon pressure was recorded for 10 hours after inflation (4 hours fasted, 2 hours during administration of 13 C‐labeled EN, and 4 hours postprandially). Gastric motility was expressed as Gastric Balloon Motility Index (GBMI), reflecting the fraction of time in which phasic gastric contractions occurred. Gastric emptying was assessed by 13 C‐octanoate breath test and expressed as gastric half‐emptying time (GET½). Correlation between GBMI (assessed in different time intervals) and GET½ was investigated by Pearson/Spearman correlation. Feasibility was defined as the success of tube placement and pressure recording. Safety was assessed based on adverse device effects. Results: Thirty patients were enrolled, of whom 19 had paired GBMI and GET½ data. There was no correlation between GBMI and GET½. The tube was successfully placed in 28/30 (93.3%) patients. In 3/28 (10.7%) patients, balloon leakage precluded analysis. Two safety events were directly linked to the device. Conclusion: This pilot study showed no significant correlation between balloon‐assessed gastric motility and emptying in critically ill patients. The feasibility/safety profile of the balloon tube appears similar to that of standard nasogastric tubes.